Multispecies hierarchies and capitalist value: Insights from salmon aquaculture. (December 2022) - Power, Nicole; Melvin, Jessica; Mather, Charles
Research in animal geographies is increasingly paying attention to hierarchies and inequalities within and between nonhuman animals. The way that animals are valued differently and hierarchically within this growing body of scholarship has tended to focus on a range of biopolitical differences between and within species. Collard and Dempsey's recent contribution, in contrast, points to the importance of hierarchy and difference in the valuation of nonhuman animals under capitalism. Their framework identifies five orientations of human and nonhuman bodies in relation to capitalist value, which in turn provides a heuristic to explore how capitalist accumulation produces and depends on differentially oriented natures. Our contribution to these debates – and to the Collard and Dempsey framework – draws on our ongoing research in Eastern Canada where salmon aquaculture is a growing yet highly contested industry. We focus on two instances of multispecies hierarchy and difference in and around the salmon cage that are central to this form of ocean-based production. In focusing on multispecies relations, we build on Collard and Dempsey's framework in two main ways. First, we show how valuation and devaluation reflect competing but relational capitalist interests, which rely on and produce different natures refracted through the logic of the nature/culture divide: Atlantic salmon are valued as game fish, and as the key species for Canada's aquaculture sector. Second, we show how capital's valuation of one species, in our case farmed salmon, implicates the valuation of others, namely sea lice and lumpfish. Our case studies extend Collard and Dempsey's framework by demonstrating how capitalist differentiation produces violence through and outside of commodification in terms of multispecies difference and hierarchy; the lives and futures of wild and farmed salmon, lumpfish and sea lice are entangled, and reflect relational and changing orientations to capitalist value over time.